EDUCATORS’ OPINION ON WEBINARS IN HIGHER EDUCATION - Ahrens, Andreas; Zascerinska, Jelena; Ramar, Hariharan; Andreeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Three strategic priorities of the European Union such as Open Innovation, Open Science, and Openness to the World reveal that higher education focused on training of students as prospective specialists needed by society and production orient higher education how to change. In higher education the transition from distance learning to on-line learning has started. For on-line learning in higher education, webinars are becoming an indispensable tool. However, educators’ opinion on webinars in higher education has not been analyzed. The aim of the present contribution is to analyze educators‘ opinion on webinars in higher education underpinning elaboration of a hypothesis on use of webinars in on-line educational environment within higher education. The meaning of such key concepts as webinar, opinion, on-line learning and on-line educational environment is studied. Moreover, the study shows how the steps of the process are related: identifying webinars → defining educators’ opinion → empirical study → conclusions. The empirical study was carried out in September 2015. The sample included 58 educators from the teacher training institution, namely Dr. Sivanthi Aditanar College of Education in India. The study results demonstrate that the educators’ opinions on webinars in higher education are homogeneous. A hypothesis on use of webinars in on-line educational environment within higher education is elaborated. Directions of further research are proposed.